Utility of Sepsis Screen in the Early Diagnosis of Neonatal Sepsis - Chandrashekhar P Bhale; Apurva Vasant Kale; Sachin S Kale; Meera Mahajan; Smita S Mulay (JCDR Research and Publications Pvt. Ltd., 2016)
Introduction: Neonatal sepsis could be defined as a clinical entity because of generalized bacterial infection within 28 days of life and showing a positive blood culture. It is probably responsible for 30- 50% of the total neonatal deaths each year. Timely diagnosis of neonatal sepsis is critical because in neonates the illness can progress more rapidly than adults. The blood culture report takes at least 72 hours. Therefore, a simple test with quick availability of results can be helpful to reduce neonatal morbidity and mortality. Aim: To evaluate the utility of sepsis screen in early diagnosis of neonatal septicemia and to study various hematological parameters, changes in peripheral blood smear, evaluate the performance of microerythrocyte sedimentation rate, serum C-reactive protein and serum direct bilirubin in neonates with clinical suspicion of sepsis. Materials and Methods: The present, study was done in our institute from October 2013 to October 2015. CBC was done on 191 clinically suspected cases of neonatal sepsis along with Micro ESR, Serum CRP and direct bilirubin. Differential leukocyte count, absolute neutrophil count, immature neutrophils: total neutrophils ratio was done from Field stained peripheral smears. Blood culture was done in Microbiology Department. Exclusion criteria were neonates with major congenital anomalies and those who have already received antibiotics. Statistical Analysis: Statistical analysis was done using SPSS software, version 20th and unpaired 't'- test. Result: Out of 191 cases studied, 91 were culture positive. CRP (84.6%) and immature : total neutrophils ratio(75.8%) showed highest sensitivity, Whereas absolute neutrophil count(99.0%) along with serum direct bilirubin (93.0%) and corrected total leucocyte count (93.0%)showed highest specificity. Positive predictive value was highest for absolute neutrophil count (97.5%) and CRP (84.8%). Conclusion: Serum CRP is the most sensitive marker of sepsis. Use of peripheral smear study, serum direct bilirubin and micro ESR together with CRP can be used effectively as a sepsis screen for early diagnosis of neonatal sepsis.